2008
DOI: 10.1002/cncr.23444
|View full text |Cite
|
Sign up to set email alerts
|

A gerontologic perspective on cancer and aging

Abstract: Most people diagnosed with cancer are aged >65 years, and many diagnosed younger live to become older survivors. Geriatric oncology is becoming recognized as a specialty area within oncology. It focuses specifically on the functional impacts of the interplay of aging and cancer, including the role of comorbidities.Nevertheless, to the authors' knowledge, little attention has been given to cancer from a gerontologic and lifespan perspective, especially quality of life and psychologic impact. Research has shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
96
1
8

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 53 publications
9
96
1
8
Order By: Relevance
“…Less aggressive care is associated with better quality of life of the 149 patient and less burden on the family after their loved one died 17 . The benefitting role of the 150 geriatrician in EOL care has recently been described to be important in the oncogeriatric patient 151 12,13,14 . Most probably, the more patient-oriented approach of geriatricians (versus the disease-152 oriented approach of other specialists) leads to a less aggressive care for the dying elderly patient 14 .…”
Section: Determinants Of Icu Referral At Eol 139mentioning
confidence: 99%
See 1 more Smart Citation
“…Less aggressive care is associated with better quality of life of the 149 patient and less burden on the family after their loved one died 17 . The benefitting role of the 150 geriatrician in EOL care has recently been described to be important in the oncogeriatric patient 151 12,13,14 . Most probably, the more patient-oriented approach of geriatricians (versus the disease-152 oriented approach of other specialists) leads to a less aggressive care for the dying elderly patient 14 .…”
Section: Determinants Of Icu Referral At Eol 139mentioning
confidence: 99%
“…The authors observed that 54% of very old patients received intensive care 27 before dying whereas most of these patients had stated that they did not want aggressive care 11 . The 28 role of the geriatrician in the assessment and management of frail elderly together with EOL care 29 has recently been described to be important in insuring a good quality of life in the oncogeriatric 30 patient 12,13,14 . 31…”
mentioning
confidence: 99%
“…With the difficulties associated with aging, it may not be surprising that distress is relatively common among the elderly. However, an initial research has shown that younger adults with cancer have a higher risk of reporting psychological distress than older adults with cancer (Blank et al, 2008). DOI:http://dx.doi.org/10.7314/APJCP.2012.13.1…”
Section: Discussionmentioning
confidence: 99%
“…Some other reports suggested that age may serve as a protective factor against psychological distress related to cancer (Carstensen et al, 2006;Blank et al, 2008;Forstmeier et al, 2008;Nelson et al, 2009). Our study demonstrates that age is associated with somatization and obsessive-compulsive tendencies as a risk factor, phobia and paranoia as a protective factor.…”
Section: 309 Factors Associated With Psychological Characteristics Imentioning
confidence: 98%
“…Moreover, older adults are more likely to have a higher number of comorbidities and decreased functional reserve; thus, the relative contribution of treatment's adverse effects to physical well-being may be paramount in the treatment decision process and successful survivorship. 3 The primary goal of any treatment is to achieve optimal ''physical, mental, and social well-being, not merely the absence of disease or infirmity.'' 4 Physical well-being, among the most important factors attributed to a person's level of independence, encompasses physical performance, functional capabilities, and energy level.…”
mentioning
confidence: 99%